DEVELOPMENT AND INVESTIGATION OF THE KEY STREAM GENERATORS ON THE BASE OF CELLULAR AUTOMATA - Val, O. D.; Zhikharevich, V. V.; Ovchar, R. I.; Ostapov, S. E. (Radio Electronics, Computer Science, Control, 2015)
This paper presents the development and investigations of the binary key stream generators statistical characteristics. Developed generators based on the elementary rules of cells interaction: simple, modified and combined classical rules. We believe that elementary rules «30», «86», «135», «149» are most promising from statistical point of view. Modifications were consist of combining of array bits before outputting and combining various elementary rules of automaton cells interaction. It was developed a new simple interaction rule, based on the logical operation XOR. The investigation of statistical properties was performed using NIST STS v1.8. All designed generators showed good statistical characteristics, which indicates their satisfactory cryptoresistance. In addition we’ve investigated the developed generators linear complexity using Berlekamp-Massey algorithm. Obtained results shows the high values of linear complexity (about half of the cellular automaton length), which is typical for such structures type. On the base of the developed generator with own cells interaction rule has developed a system for secure communication of audio, text and file information. The statistical investigations of encrypted file showed that it satisfies all the NIST STS requirements.